2002
DOI: 10.1093/emboj/cdf620
|View full text |Cite
|
Sign up to set email alerts
|

Exportin-5-mediated nuclear export of eukaryotic elongation factor 1A and tRNA

Abstract: Transport of proteins and RNA into and out of the cell nucleus is mediated largely by a family of RanGTP‐binding transport receptors. Export receptors (exportins) need to bind RanGTP for efficient loading of their export cargo. We have identified eukaryotic elongation factor 1A (eEF1A) and tRNA as RanGTP‐dependent binding partners of exportin‐5 (Exp5). Exp5 stimulates nuclear export of eEF1A when microinjected into the nucleus of Xenopus laevis oocytes. Surprisingly, the interaction between eEF1A and Exp5 is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
185
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(198 citation statements)
references
References 43 publications
9
185
1
2
Order By: Relevance
“…It has also been shown that interaction between in vitro translated ILF3 and exportin-5 was affected upon RNase treatment suggesting that the complex between these proteins was RNA-mediated (8).…”
Section: Ilf3mentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that interaction between in vitro translated ILF3 and exportin-5 was affected upon RNase treatment suggesting that the complex between these proteins was RNA-mediated (8).…”
Section: Ilf3mentioning
confidence: 99%
“…eEF1A is a GTP-binding protein that interacts with aminoacetylated tRNA and catalyzes their binding to the ribosome. Complex formation between eEF1A and exportin-5 was shown to be strictly dependent on aminoacetylated tRNAs that bridge both proteins (8,9). Indeed, tRNAs present a highly degenerated minihelix motif able to directly interact with exportin-5, although with a lower affinity than an optimal minihelix structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…52 They interact with the importin-and exportin-mediated transport of proteins in and out of the nucleus. 53 Three clones of the PTX induced genes exhibit similarity to the same asparaginyl b-hydroxylase mRNA transcribed from ASPH (clone 1.20, 1.27 and 1.28). Conservation of this gene up till human species suggests that the ASPH holds important functional roles.…”
Section: Insert-comparison With Genomic Databasesmentioning
confidence: 98%
“…The mamallian (Exp5) and Drosophila (dmExp5) orthologs of Msn5 have also been implicated in tRNA transport (Bohnsack et al 2002;Calado et al 2002;Shibata et al 2006). Defects in tRNA re-export can be monitored by genetic and biochemical means.…”
Section: Introductionmentioning
confidence: 99%